2003
DOI: 10.1097/01.mp.0000093627.51090.3f
|View full text |Cite
|
Sign up to set email alerts
|

Expression of B-Cell Markers in Classical Hodgkin Lymphoma: A Tissue Microarray Analysis of 330 Cases

Abstract: Hodgkin and Reed-Sternberg cells of classical Hodgkin lymphoma arise from B-lymphocytes. However, classical markers of the B-cell phenotype, such as CD20, are present only in about 25% of the cases. The aim of the present study was to assess expression of the B-cell-related antigens CD20, CD79a, and CD138 in classical Hodgkin lymphoma using a tissue microarray consisting of 330 classical Hodgkin lymphoma cases. Expression of CD15, CD20, CD30, CD79a, CD138, and latent membrane protein 1 of Epstein-Barr virus wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
79
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(88 citation statements)
references
References 30 publications
7
79
1
1
Order By: Relevance
“…Several proteins that regulate the mitotic cycle, such as cyclin D1, D3, E, B1, cyclin-dependent kinases 1, 2 and 6, S-phase kinase associated protein-2, p16 INK4A , p18 INK4c , p21 CIP1 , p27 KIP1 , p53, the retinoblastoma protein and PCNA have been found to be deregulated in classical Hodgkin's lymphoma. [1][2][3][4]6,[20][21][22][23][24][25][26] In the present study, we used a previously validated classical Hodgkin's lymphoma tissue microarray with a cohort of clinically well-documented cases 6,17,27 to analyze the expression of the cyclin-dependent kinase inhibitors of the Cip/Kipfamily, p21 CIP1 and p27 KIP1 , as well as two proliferation markers, PCNA and cyclin A. Since Hodgkin and Reed-Sternberg cells are embedded within reactive normal lymphocytes, we used those lymphocytes as internal controls for our staining Aberrant cell cycle regulation in Hodgkin's lymphoma A Tzankov et al conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteins that regulate the mitotic cycle, such as cyclin D1, D3, E, B1, cyclin-dependent kinases 1, 2 and 6, S-phase kinase associated protein-2, p16 INK4A , p18 INK4c , p21 CIP1 , p27 KIP1 , p53, the retinoblastoma protein and PCNA have been found to be deregulated in classical Hodgkin's lymphoma. [1][2][3][4]6,[20][21][22][23][24][25][26] In the present study, we used a previously validated classical Hodgkin's lymphoma tissue microarray with a cohort of clinically well-documented cases 6,17,27 to analyze the expression of the cyclin-dependent kinase inhibitors of the Cip/Kipfamily, p21 CIP1 and p27 KIP1 , as well as two proliferation markers, PCNA and cyclin A. Since Hodgkin and Reed-Sternberg cells are embedded within reactive normal lymphocytes, we used those lymphocytes as internal controls for our staining Aberrant cell cycle regulation in Hodgkin's lymphoma A Tzankov et al conditions.…”
Section: Discussionmentioning
confidence: 99%
“…6,17 Sections of the tissue microarray blocks, 4 mm thick, were transferred to an adhesive-coated glass slide system (Instrumedics Inc., Hackensack, NJ, USA) and stained with hematoxylin and eosin, Giemsa and with the periodic acid Schiff reaction. Only cases containing at least two morphologically unequivocal Hodgkin and Reed-Sternberg cells were analyzed.…”
Section: Construction Of Tissue Microarrays and Morphological Analysismentioning
confidence: 99%
“…1 In contrast, Reed-Sternberg and Hodgkin's cells in classical Hodgkin's lymphoma, despite their rearranged immunoglobulin genes, fail to express functional immunoglobulin mRNA and/or protein, and lack B-cell-specific antigens in most instances. [1][2][3][4] It has been speculated that the lack of immunoglobulin mRNA transcripts and immunoglobulin protein expression, as well as B-cell specific antigens may be due to either crippling mutations of the immunoglobulin genes found in approximately 25% of cases, 2,[5][6][7] or downregulation and disruption of the B-cell-specific transcription factors. [8][9][10] Recent studies have shown that transcription factors Pax-5, Oct-1, Oct-2, BOB.1, and PU.1 are expressed in the majority of B-cell lymphomas and nodular lymphocyte predominant Hodgkin's lymphoma, but are downregulated in Reed-Sternberg and Hodgkin's cells of classical Hodgkin's lymphoma.…”
mentioning
confidence: 99%
“…In addition, in a significant proportion of classical Hodgkin's lymphoma, the Reed-Sternberg and Hodgkin's cells lack B-cellspecific antigens. [1][2][3][4] The lack of immunoglobulin mRNA transcripts and proteins as well as B-cell specific antigens have been speculated to be due to either crippling mutations of the immunoglobulin genes found in about 25% of cases, 2,5-7 or downregulation and disruption of the B-cell-specific transcription factors. [8][9][10] In contrast to classical Hodgkin's lymphoma, the neoplastic cells in nonHodgkin's lymphomas of B-lineage and nodular lymphocyte predominant Hodgkin's lymphoma express B-cell-specific antigens, immunoglobulin mRNA transcripts and their proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation